Effective flocculation of Chlorella vulgaris using chitosan with zeta potential measurement - Low, Y.; Lau, Shiew Wei (2017)
© Published under licence by IOP Publishing Ltd. Microalgae are considered as one promising source of third-generation biofuels due to their fast growth rates, potentially higher yield rates and wide ranges of growth conditions. However, the extremely low biomass concentration in microalgae cultures presents a great challenge to the harvesting of microalgae because a large volume of water needs to be removed to obtain dry microalgal cells for the subsequent oil extraction process. In this study, the fresh water microalgae Chlorella vulgaris (C. vulgaris) was effectively harvested using both low molecular weight (MW) and high MW chitosan flocculants. The flocculation efficiency was evaluated by physical appearance, supernatant absorbance, zeta potential and solids content after centrifugal dewatering. High flocculation efficiency of 98.0-99.0% was achieved at the optimal dosage of 30-40 mg/g with formation of large microalgae flocs. This study suggests that the polymer bridging mechanism was governing the flocculation behaviour of C. vulgaris using high MW chitosan. Besides, charge patch neutralisation mechanism prevailed at low MW chitosan where lower dosage was sufficient to reach near-zero zeta potential compared with the high MW chitosan. The amount of chitosan polymer present in the culture may also affect the mechanism of flocculation.